Electronic perturbation of Pd single-atom catalysts on graphdiyne derivatives toward effective electrocatalytic nitrate reduction - Cheng Wang; Tao Song; Hao Dai; Siyan Shu; Shenghan Zhang; Hongliang Dong; Yongfei Ji; Lele Duan (ChemPhysMater)
Electrocatalytic reduction of nitrate (NO3−) to ammonia (NH3) is a promising approach for addressing water pollution caused by nitrate and producing industrial feedstock NH3. However, a significant challenge lies in effectively suppressing the formation of undesired byproducts such as H2, N2, NO2−, and N2H4. In this study, three Pd single-atom catalysts (SACs) supported on graphdiyne (GDY) derivatives functionalized with electron-withdrawing and electron-donating groups denoted as Pd/GDY-F, Pd/GDY-H and Pd/GDY-OMe were prepared. Structural characterization showed that due to the electron induction effect of the functional groups, Pd/GDY-F displays the highest Pd valence state, followed by Pd/GDY-H and Pd/GDY-OMe. Interestingly, the nitrate reduction activity also follows the order Pd/GDY-F > Pd/GDY-H > Pd/GDY-OMe, indicating that the nitrate reduction activity of Pd depends on the Pd oxidation state. In addition, the anion exchange ionomers and high nitrate concentrations are beneficial for nitrate reduction. Under optimized conditions, Pd/GDY-F displays a high Faraday efficiency (FE) of 96.2% ± 2.5% toward NH3. Mechanistic studies revealed that high-valence Pd atoms favor the adsorption of nitrate reduction intermediates, leading to a high Faraday efficiency for NH3.